PERAN PSIKOLOGI PENDIDIKAN UNTUK MENINGKATKAN HASIL BELAJAR MELALUI PEMBELAJARAN BERDIFERENSIASI DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Endang Komara; Sylviana Stefanie; Riska Irnawati; Tita Agustini (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study is to investigate the role of educational psychology in the classroom. This study employs an ethnomethodological strategy within a systems research framework. The major goal of this study is to get an in-depth knowledge of the function of educational psychology in attempts to enhance learning outcomes via differentiated learning in the implementation of the autonomous curriculum. Understanding how pupils take in information, react to stimuli, and push through barriers is what educational psychologists’ study in great detail. By using what we know about educational psychology in the classroom, we can help every student develop to his or her fullest potential in a setting that fosters learning and encourages personal development. Thus, educational psychology is not only a field of study, but also a powerful resource for improving and expanding access to quality education in the years to come